Effect of protein source on in situ digestibility of sugarcane silage-based diets - Reyes-Gutiérrez, José Andrés; Montañez-Valdez, Oziel Dante; Guerra-Medina, Cándido Enrique; Ley de Coss, Alejandro (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2020)
The objective of this study was to evaluate the effect of the protein source in sugarcane silage-based diets on the ruminal pH and in situ dry matter digestibility (DMD). The treatments were: 1)- 60% sugarcane silage + 15% soybean meal (SBM); 2)- 60% sugarcane silage + 15% fish meal (FM); 3)- 55% sugarcane silage + 20% canola meal (CM); and T4)- 50% sugarcane silage + 30% coconut meal (CCM). In situ DMD was determined by the nylon bag technique using four cows equipped with ruminal cannula. Five grams of each experimental diet were weighted in nylon bags and incubated for 8, 12, 24, 48, 72 and 96 h. Dry matter digestibility for SBM, CM, and CCM showed higher values compared to FM. A similar pH among treatments was recorded; however, at 4 h decreases in SBM and FM were observed. Sugarcane silage in integral diets with the different protein sources used in this study, did not modify ruminal pH but showed lower DMD when fish meal was the protein source. Highlights The use of bacterial inoculum and an additive that promotes the silage process of sugarcane and improves its quality. Use of sugarcane silage and soybean meal as a protein source increase the ruminal digestibility of dry matter of the diet, and not change ruminal pH. Sugarcane silage can be used as an ingredient in an integral diet for ruminants.